2009
DOI: 10.5539/jsd.v1n1p13
|View full text |Cite
|
Sign up to set email alerts
|

Human Disturbance, Natural Resilience and Management Futures: The Coral Reefs of Todos Os Santos Bay, Bahia, Brazil

Abstract: Between 1962 and 2003 significant coral species changes within reef assemblages at Todos os Santos Bay (TSB), Bahia (Brazil) have taken place, following what appears to have been a 400 year contraction of coral reefs from the inner, landward reaches of the bay. The last 40 years in particular encompassed rapid and extensive urban and industrial development its surrounding lands, which contributed to coral reef changes. However, changes in this environment have influenced coral reef resilience since the arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Changes in the community may be triggered by natural or anthropogenic disturbances (Connell & Sousa ; Minchinton ); in the BTS the phase shifts are thought to be linked to a number of human stressors (Dutra & Haworth ), which may have synergistic effects. Reporting on surveys carried out within the TSB in 2003, Dutra et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the community may be triggered by natural or anthropogenic disturbances (Connell & Sousa ; Minchinton ); in the BTS the phase shifts are thought to be linked to a number of human stressors (Dutra & Haworth ), which may have synergistic effects. Reporting on surveys carried out within the TSB in 2003, Dutra et al .…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the community may be triggered by natural or anthropogenic disturbances (Connell & Sousa 1983;Minchinton 2007); in the BTS the phase shifts are thought to be linked to a number of human stressors (Dutra & Haworth 2008), which may have synergistic effects. Reporting on surveys carried out within the TSB in 2003, Dutra et al (2006) suggested that human impacts may have been responsible for the loss of the coral species Mussismilia braziliensis and Meandrina braziliensis, the hydrocoral Millepora nitida and all octocorals.…”
Section: Resultsmentioning
confidence: 99%
“…In China this may be because of a lack of will perhaps due to production pressures or a lack of knowledge, whereas in Poland this is really due to the lack of deployment of knowledge and a fear of punishment for asking for money to improve the system. Rather than the socio-cultural resilience of an organization, with the ability to absorb changes and still function, proposed by Dutra and Hayworth (2008), the study factories exhibited a socio-cultural resistance to change which will prejudice it's own and other sustainability's.…”
Section: Sewage and Waste Arisings And Effectsmentioning
confidence: 94%
“…Para os metais-traço (Zn, Cu, Cr, Ni e Pb), avaliados em uma mesma região da Austrália, Goniastrea aspera 50,51 exibiu muito mais Zn em seu esqueleto do que Pocillopora damicornis. 22,50 No mar arábico, Montipora digitata 53 Outros fatores, como o aumento do aporte de íons metálicos para esta região, também podem ter contribuído para o desaparecimento destas espécies. As espécies mais resistentes a condições estressantes observadas na Baía de Todos os Santos foram Montastrea cavernosa e Siderastrea stellata.…”
Section: Utilização De Corais Como Organismos Biomonitoresunclassified